1990
DOI: 10.1037/0022-006x.58.4.432
|View full text |Cite
|
Sign up to set email alerts
|

Self-instruction to prevent HIV infection among African-American and Hispanic-American adolescents.

Abstract: This study tested the efficacy of self-instruction intervention to reduce avoidable risks for HIV infection associated with drug use and unsafe sexual activity among African-American and Hispanic adolescents (N = 60). After completing pretests, adolescent participants in the study were randomly divided into three conditions. Participants in one condition received a self-instructional guide about AIDS and its transmission along with group instruction in using the guide. Adolescents in another condition received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…In short, they found that behaviour skills training was effective in lowering black male adolescents' sexual risk behaviour. However, another study by Schinke, Gordon and Weston (1990) that evaluated a cognitive intervention with minority youths found that although the youths learned problem-solving skills, their cognitive acquisition did not transfer into any measurable behaviour changes lowering their HIV infection risk.These two studies provide conflicting evidence on whether it is cognitive acquisition transfer into behaviour changes that lowers adolescents' HIV infection risk.…”
Section: Letter To the Editormentioning
confidence: 92%
“…In short, they found that behaviour skills training was effective in lowering black male adolescents' sexual risk behaviour. However, another study by Schinke, Gordon and Weston (1990) that evaluated a cognitive intervention with minority youths found that although the youths learned problem-solving skills, their cognitive acquisition did not transfer into any measurable behaviour changes lowering their HIV infection risk.These two studies provide conflicting evidence on whether it is cognitive acquisition transfer into behaviour changes that lowers adolescents' HIV infection risk.…”
Section: Letter To the Editormentioning
confidence: 92%
“…instruction, simulation games, and structured discussions). According to Schinke, Gordon, and Weston (1990) , labeling and stigmatization can be avoided by employing a model that uses learning theory to explain problem behaviors and at the same time encourage proactive behaviors. Learning theory gives the subject control, creating expectation and confi dence in the individual ' s ability to change, while simultaneously emphasizing that negative behaviors can be unlearned and replaced by positive ones.…”
Section: Basic Concepts and Skills Targeted In The Programsmentioning
confidence: 99%
“…The curriculum was developed by Orbis Associates, an American Indian-controlled, not-for-profit education organization, with support of the BIA Office of Education and the Centers for Disease Control and Prevention-Division of Adolescent and School Health. Based on earlier research in HIV-prevention education (Schinke et al 1990), COL was designed as a targeted health curriculum for HIV and STD prevention with an emphasis on skills-building and role-playing. Consistent with American Indian philosophies, however, it encompassed far more than sexual-risk prevention—it promoted the development of overall wellness of students.…”
Section: Interventionmentioning
confidence: 99%